Ileosigmoid Knot: A Case Report - Nazir, Shahid; Munir, Ambreen; Sulman, Sahrish; Waleed, Qazi Muhammad; Yar Muhammad, Aisha (Journal of Liaquat University of Medical & Health Sciences, 2020)
Ileosigmoid knot (ISK) is a very infrequent and unusual reason of intestinal obstruction and treated as a surgical emergency. In this disorder ileum usually encircled around base of sigmoid colon and make a pseudo knot. ISK is very infrequent disorder in Western countries as compared to Asian countries. Its diagnosis is very difficult because it’s a rare disease with limited sensitive and specific diagnostic tests available, hence it’s only found intraoperative; that results in high mortality. In this case study, a 20-year male adult was presented with ISK. In this case study a 20-year male adult, admitted in surgical department on December 2018, with a severe abdominal pain, and constipation from last three days, three episodes of bilious vomiting, and high-grade fever from last 24 hours. Past medical and surgical history of patient was non-significant. X-ray showed a marked dilation in small bowel loops. During surgery, massive volvulus involving descending colon and sigmoid colon was observed, along with ileum was twisting around the volvulus, affected segments were resected and patients was managed appropriately and discharged.